HUBUNGAN ANTARA KEMAMPUAN EMOSI DENGAN KEMANDIRIAN ANAK USIA DINI 5-6 TAHUN - Ramdani, Cepi; Nuraini; Purwani Kusumawati Wijaya (Al Hanin, 2025)
The main issue in this research is whether emotional abilities can affect the independence of children aged 5-6 years at RA Nurul Anwar Bekasi Timur. This study aims to determine whether there is a relationship between emotional abilities and the independence of early childhood children aged 5-6 years in Bekasi Timur. The research uses one group, which is the group of 5-6-year-old children (Group B). This research is a descriptive quantitative study with a correlational method. Correlational research is a non-experimental type of study that uses two variables, aiming to understand and assess the statistical relationship between them without the influence of external variables. Data collection is done using instruments and percentage calculations. The sampling technique used in this study is random sampling or cluster random sampling. Cluster random sampling is used to select samples based on regions (clusters) within the population. In this study, the researcher conducted direct observations in the field and analyzed the results of the instruments applied to the children. Additionally, data were supported by several references such as books and journals related to emotional abilities and child independence. Data analysis involved normality tests, homogeneity tests, simple linear regression analysis, linearity tests, and product moment correlation tests. The research results from observations conducted at RA Nurul Anwar using the product moment showed a coefficient value of 0.578, indicating a moderate correlation between emotion (X) and independence (Y). This means that the relationship between emotional abilities (X) and independence (Y) is considered moderate, with a positive correlation. This suggests that as emotional abilities (X) increase, independence (Y) also increases, and both variables move in the same direction. The linearity test revealed a significance value for deviation from linearity of 0.180, which is greater than 0.05, indicating a linear relationship between emotion (X) and independence (Y). Based on the findings, it can be concluded that there is a relationship between emotional abilities and the independence of children aged 5-6 years at RA Nurul Anwar.